Benefits of an interdisciplinary stroke clinic: addressing a gap in physical therapy at post-stroke neurology follow-up. Issue 26 (18th December 2022) - Nagaraja, Nandakumar; Kraus, Alison R.; Rose, Dorian K.; Olasoji, Esther B.; Khanna, Anna Y.; Simpkins, Alexis N.; Wilson, Christina A.; Dickens, Rondalyn R.; Shushrutha Hedna, Vishnumurthy; Geis, Carolyn; Youn, Teddy; Musalo, Michelle M.
Abstract: Background and purpose: An interdisciplinary stroke clinic (ISC) can improve communication and identify people post-stroke who have not reached their full recovery potential. We describe the characteristics of participants who underwent physical therapy (PT) evaluation in addition to their outpatient neurology evaluation and identify the association of assessment scales that predicted referral for additional rehabilitation. Methods: Participants' post-stroke seen in the ISC were included in the study. The PT evaluation included the Berg Balance Scale (BBS), Ten-Meter Walk Test (10MWT), Six-Minute Walk Test (6MWT), and Short Form-Stroke Impact Scale (SF-SIS). Multivariable logistic regression analysis was performed to identify factors associated with referral for additional rehabilitation. Results: The study consisted of 148 participants with a mean age of 63 ( SD  ± 15) years; 58% were women and 76% were Whites. Additional rehabilitation was recommended for 59% of participants. In multivariate analysis, reduced speed on comfortable 10MWT (OR = 0.06; 95%CI = 0.01–0.51) and lower SF-SIS score (OR = 0.76; 95%CI = 0.66–0.87) were significantly associated with referral for additional PT or occupational therapy. Conclusion: A significant number of post-acute stroke survivors were found to be appropriate for additional rehabilitation when assessed clinically by a neurologic physical therapist in an ISC. The measures that most closely correlated with this in-person clinical evaluation were 10MWT and SF-SIS. IMPLICATIONS FOR REHABILITATION: An interdisciplinary stroke clinic can improve communication and identify people post-stroke who have not reached their full recovery potential. In a pilot study, a significant number of post-acute stroke survivors were found to be appropriate for additional rehabilitation when assessed clinically by a neurologic physical therapist in an interdisciplinary stroke clinic. Reduced speed on comfortable Ten-Meter Walk Test and lower Short Form-Stroke Impact Scale scores were associated with referral for additional rehabilitation.